1991
DOI: 10.1161/01.cir.83.4.1210
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for structural sympathetic reinnervation after orthotopic cardiac transplantation in humans.

Abstract: Early after CT, neither tyramine nor handgrip exercise caused a significant cardiac release of NE, suggesting sympathetic denervation. Late after CT, most patients had a significant, but subnormal, NE release in response to pharmacological or reflex stimuli, suggesting that limited sympathetic reinnervation occurs in most patients after orthotopic CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
116
0
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(129 citation statements)
references
References 33 publications
11
116
0
1
Order By: Relevance
“…It has also been shown that reinnervation remains regionally heterogeneous. 6,7,9,28 Consistently, with the use of PET methodology, which allows direct detection of reappearing myocardial catecholamine uptake and storage, evidence of incomplete reinnervation was found in the present study. Previous work has shown that sympathetic reinnervation contributes to partial restoration of exercise capacity 29 and plays a role for regulation of myocardial blood flow and metabolism.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…It has also been shown that reinnervation remains regionally heterogeneous. 6,7,9,28 Consistently, with the use of PET methodology, which allows direct detection of reappearing myocardial catecholamine uptake and storage, evidence of incomplete reinnervation was found in the present study. Previous work has shown that sympathetic reinnervation contributes to partial restoration of exercise capacity 29 and plays a role for regulation of myocardial blood flow and metabolism.…”
Section: Discussionsupporting
confidence: 89%
“…Prolonged hypothermic ex vivo storage, 1 episodes of rejection, 2 effects of immunosuppressive therapy, 3 and transplant vasculopathy 4 may all alter the functional and metabolic state. Myocardial sympathetic denervation as the result of surgical interruption of postganglionic nerve fibers 5 is another factor that has been discussed to influence allograft performance by a reduction of local myocardial catecholamine uptake, storage, and release 6,7 and an impaired responsiveness to adrenergic stimulation. 8 Conversely, reappearance of innervation, which has been demonstrated late after transplantation, 6,7 may resolve changes in the denervated heart.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11,[14][15][16] In addition, experiments suggest catecholamine uptake, storage or release from presumed cardiac sympathetic postganglionic neurons in the transplanted heart. 15,[17][18][19] Evidence for parasympathetic reinnervation derives from reports of a high-frequency variability in HR in a small number of transplants, 20,21 and the demonstration of atropine-sensitive reflex changes in HR. 22 In addition, there are a few reports describing vasovagal syncopal-like episodes in cardiac transplant patients.…”
mentioning
confidence: 99%
“…Such changes in HR are of particular interest when considered in the context of the controversy regarding reinnervation of the transplanted organ. 1 As the patient had undergone transplantation only five months previously, and, as reinnervation of the transplanted heart (when demonstrable) is not evident before one year after transplantation, 14,18,19,26 the response is unlikely to have been mediated by reflex activation of the sinoatrial (SA) node directly via the central nervous system. Because the patient underwent transplantation using the bicaval anastomosis technique, changes in donor HR could not have been mediated by altered rate of contraction of remnant innervated atrial tissue.…”
mentioning
confidence: 99%